Three centuries of dynamics in the lowland section, induced by human impact – a sociogeomorphic approach - Timofte, Fabian; Urdea, Petru (Geographica Pannonica, 2022)
This study aims to analyze one of the most dynamic sections in the lower part of the Mureș River, Lipova-Arad sector. The geological and tectonic context influenced the shifts of the watercourse at both a regional scale and a local one. The channelization works have shortened the length of the channel by 1/3 of it. The flood events in the 70s and the mining activity have also influenced the evolution of the river in last decades. Accelerating the geomorphological processes, mostly after the great floods, have narrowed the channel by 35%, and have reduced the total islands surface by almost 80%. In this context, the Mureș River try to reach the dynamic equilibrium state had before the human interventions. Under the anthropic pressure the geomorphological processes have been accelerated and the landscape left behind in Lipova-Arad section, along the Mureș River suffered important changes.